Enhancement of surface properties of nanocrystalline TiN coated plasma nitrided AISI 310 austenitic stainless steel. (2017) - Singh, Pankaj Kumar; Kumar, Arbind; Sinha, Sanjay Kumar; Aggarwal, Aman; Singh, Gajendra Prasad
The surface modification with combination of plasma nitriding and TiN coating on 310 stainless steel significantly improved the surface hardness and corrosion properties. X-ray diffraction showed the expanded austenite, CrN and TiN phases along with austenite phase. The nitrided layer was found in 10-50 μm range and the TiN layer was about 200 nm. The Raman band at 803 cm −1 corresponds to an untreated sample. The bands at 220 cm −1, 250 cm −1, and 468 cm −1 is for CrN/Cr2N and at 280 cm −1 and 589 cm −1 for TiN. The hardness is increased from 1.6 GPa to 10.4 GPa after coating. The corrosion current density about 4.6 × 10 −7 Acm −2 was measured and the ICR was reduced from 90 mΩcm 2 to 11 mΩcm 2 at 150 N cm −2 after coating. The enhancement in conductivity after coating is due to conductive nature of TiN particles which might be providing a path for electron transportation.